Hubungan Pola Asuh dengan Kecerdasan Emosional Anak Usia Sekolah - Arista Rachmawati; Thatit Nurmawati (Journal of Ners and Midwifery, 2014)
ABSTRACTIntroduction: Parenting is an interaction between the child’s parents and the parents include educating, guiding, disciplining and protecting children. Chilren who reach school age children will learn the the principles and rules. The ability to control emotions depending on the level of intelligence emosinalnya includes recognizing, understanding, controlling and using emotion. The purpose of of this study was to determine the correlation between parenting parents with emotional intelligence in children of school age ( 7-12 years). Method: Research design was analytic with cross sectional approach.  Research sample was 97 in  primary school of Sambigede 03 Blitar on May 14th, 2012,its choosed with total sampling.  Data collected by questionnaire. Analysis using Spearmen Rank test, with p≤0.0.  Result: The result showed that association between parenting  with emotional intelligence in children of school age (7-12) years, with a = 0.000 and correlation coefficient of 0.633. Discussion: Parents with an authoritative parenting have good emotional intelligence children . Keywords : parenting, emotional intelligence , school-age children